2007
DOI: 10.1002/jsfa.2864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Camelina sativa expeller cake on performance and meat quality of broilers

Abstract: The experiment was conducted to measure the effects of Camelina sativa expeller on the performance of broiler chickens and on the sensory quality and fatty acid composition of broiler meat. One-day-old broiler chickens were randomly allocated to the three dietary treatments which lasted 37 days. Experimental diets contained 0, 5 or 10% C. sativa expeller. Feed and water were offered ad libitum. The birds were weighed at the beginning, at 14 days and at the end of the trial at 37 days. Feed intake was recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 16 publications
(20 reference statements)
3
55
1
2
Order By: Relevance
“…In German pig feeding trials, depression of growth rate, deterioration of consistency of carcass fat, and a decrease in meat palatability occurred when the percentage of C. sativa expeller (pressed oilseed residues) exceeded 5% of the pigs' diet , while Flachowsky et al (1997) found that feeding C. sativa expellers to pigs resulted in a decrease in the induction time of fat development and destruction of the antioxidant vitamin E. Ryha¨nen et al (2007) found that while C. sativa seed cake added to the diet of chickens could enhance omega-3 fatty acids in the meat without affecting the flavour, the overall effects were negative, because of weight loss, depressed feed intake and a lower feed conversion level.…”
Section: Description and Account Of Variationmentioning
confidence: 99%
“…In German pig feeding trials, depression of growth rate, deterioration of consistency of carcass fat, and a decrease in meat palatability occurred when the percentage of C. sativa expeller (pressed oilseed residues) exceeded 5% of the pigs' diet , while Flachowsky et al (1997) found that feeding C. sativa expellers to pigs resulted in a decrease in the induction time of fat development and destruction of the antioxidant vitamin E. Ryha¨nen et al (2007) found that while C. sativa seed cake added to the diet of chickens could enhance omega-3 fatty acids in the meat without affecting the flavour, the overall effects were negative, because of weight loss, depressed feed intake and a lower feed conversion level.…”
Section: Description and Account Of Variationmentioning
confidence: 99%
“…Araştırmada DYA ve TDYA değerleri normal sınırlar içerisinde olup cinsiyet ve beslenme grupları arasındaki farklılık önemsizdir (25). İnsan sağlığı için faydalı yağ asitleri olarak bilinen ADYA ve Omega-6'nın deneme grupların-da yüksek bulunması (16,35) bir avantaj olarak değerlen-dirilebilir. Deneme gruplarında muhtemelen kısıtlı beslenme sonucu antikor titreleri 1. kesimde düşüktür.…”
Section: Tartışma Ve Sonuçunclassified
“…Etin dış görünüşü ile ilgili yapılan çalışmalarda farklı sonuçlar elde edilmiştir (13,15,33). Yağ asitleri, yapılarında çift bağlı karbon atomunun bulunmaması, bir tane bulunması ve birden fazla bulunması; doymuş (DYA), tek doymamış (TDYA) veya aşırı doymamış (ADYA) gruplara ayrılır (35). TDYA ve ADYA'nın DYA'a oranının yüksek olması istenilir (16).…”
Section: Introductionunclassified
“…Feeding Camelina meal to broilers led to a noteworthy increase in -linolenic acid (18:3) and longer chain -3 fatty acids, such as docosapentaenoic acid (22:5), docosahexaenoic acid (22:6) and eicosapentaenoic acid (20:5) in breast (white), thigh (dark) meat, liver and adipose tissues. The fatty acid content increase in meat and tissues was directly proportional to the percentage of Camelina meal incorporated into the feed (Ryhänen et al 2007). In another study, it was revealed that -tocopherol levels in thigh meat of hens upon feeding with CM prevented the lipid peroxidation in the respective tissue.…”
Section: Feed Of Broiler Birdsmentioning
confidence: 99%
“…CM feeding to broilers neither affected the physical characteristics such as body weight gain, carcass weight, and weights of major edible organs, nor the sensory qualities (taste, juiciness and tenderness) of broiler meat (Aziza et al, 2010b). Despite many advantageous effects, feeding hens with more than 10% CM impaired feed intake and reduced the feed conversion rate in broilers and Turkey poults in the starter phases of the study (Ryhänen et al, 2007;Frame et al, 2007), CM also caused deprivation in feed efficiency of broilers (Aziza et al, 2010b). …”
Section: Feed Of Broiler Birdsmentioning
confidence: 99%